Identification of medium‐grain rice based on GS3, a gene linked to rice grain size - Bui Phuo Tam; Pham Thi Be Tu; Nguyen Thi Pha (Universitas Gadjah Mada, 2024)
Previous studies have used molecular markers associated with the GS3 gene to differentiate between short and long rice. However, there are three classifications of grain size: long, short, and medium. The identification of medium‐grain rice using these markers linked to the GS3 gene is yet to be confirmed. Hence, this study aimed to identify medium‐grain rice through phenotyping and genotyping. Grain characteristics including grain length (GL), grain width (GW), and the length‐to‐width ratio (GL/GW) were measured using SmartGrain software. The genotype was then amplified with the GS3 gene‐linked DRR‐GL (double round‐robin for grain length) molecular marker. The results revealed that medium‐grain rice, as identified by the DRR‐GL marker, exhibited DNA bands at the position of 150 bp. These bands differed from those observed in long‐grain rice, but they were consistent with those found in short‐grain rice. The genotypic results further indicated that PCR products obtained with the DRR‐GL marker in medium‐grain rice accounted for 86.8% of the phenotypic variation in grain size. This study provides fundamental genetic insights into the identification of medium‐grain rice and contributes to optimizing effects on rice breeding related to grain size.